ASSESSMENT OF THE ACTUAL AND POTENTIAL EPIDEMIOLOGYCAL SITUATION OF THE VIRAL HEPATITIS C AND B BASED BY LABORATORY DATA IN THE "DOCTOR PARAMONOV'S CLINIC" IN SARATOV CITY AND SARATOV REGION - V.V. NIKITINA; V.A. PARAMONOV; G.P. GLADILIN; I.L. IVANENKO (Avicenna Tajik State Medical University, 2017)
Objective: Study of the prevalence of the viral hepatitis C and viral hepatitis B in the territory of Saratov City and Saratov Region, analysis of the revealed cases and discussion of laboratory diagnostics issues. Methods: Statistical and reporting forms were used in the CJSC «Doctor Paramonov's Clinic» in Saratov City, immunoenzyme method of testing blood serum which identify antibodies and antigens, and statistical analysis. Results: Analysis of the received data shows the increasing number of persons, who tested for viral hepatitis C and B. A tendency of annual increase of infected among tested persons are observed. Prolonged absence of rich clinical presentation complicates the process of actual diagnose arrangements. Conclusion: Results of the research dictate the need of a wide examination of patients, which will provide a high detectability, timely treated patients with hepatitis C and B, will assist the reduction of prevalence of these kind of viruses.